Location of Intracerebral Hemorrhage Affects Outcome After Minimally Invasive Endoscopic Hematoma Evacuation. (1st September 2019) - Song, Rui; Nistal, Dominic A; Scaggiante, Jacopo; Chartrain, Alexander G; Romano Spica, Natalia; Kleitsch, Julianne; Liang, John; Mocco, J D; Kellner, Christopher P
Abstract: INTRODUCTION: Treatment for intracerebral hemorrhage (ICH) has been largely medical after negative findings from trials evaluating open craniotomy for hematoma evacuation. Location of hemorrhage has always been a determinant of outcome in ICH. This has ramifications for outcomes after minimally invasive (MIS) evacuation. We present analysis of ICH outcome after endoscopic evacuation stratified by hemorrhage location. METHODS: Minimally invasive endoscopic ICH evacuation was performed on patients with supratentorial ICH who fit previously published clinical criteria including age = 18, National Institutes of Health Stroke Scale (NIHSS) = 6, hematoma volume = 15, and baseline modified Rankin Score (mRS) = 3 with a computed tomography angiography (CTA) negative for vascular malformation. Retrospective review was performed on patients who were treated in a single health system from December 2015 to August 2018. Hematoma location was stratified as deep or lobar. Univariate analysis and multivariate logistic regression were performed on demographic, radiographic, and clinical outcomes including the location variable with 6 mo mRS as the primary outcome measure. RESULTS: Univariate analysis revealed patients with lobar hemorrhage had significantly better initial admission Glasgow Coma Scale (GCS) (11.7 vs 8.9, P < .0001) and NIHSS score (13.7 vs 19.6, P < .0001) but significantly higher preoperative volume (64.1 vs 41.4, P = .001). Those with lobar hemorrhage also had significantly lower neurosurgical and hospital length of stay (8.1 vs 12.9, P = .003 and 16.9 vs 29.0, P = .02, respectively) and higher rate of 6 mo functional independence as defined by mRS 0 to 3 (68.6% vs 31.2%, P = .001). Multivariate analysis showed lobar location was a significant predictor of functional independence at 6 mo (OR 12.8, P = .003). CONCLUSION: In our experience, lobar hemorrhage is a predictor of good outcome after endoscopic ICH evacuation. Current and future trials may benefit from stricter patient selection and further studies are needed to confirm the effect of hemorrhage location on outcome.